2009
DOI: 10.1093/cvr/cvp265
|View full text |Cite
|
Sign up to set email alerts
|

NTPDase1 (CD39) controls nucleotide-dependent vasoconstriction in mouse

Abstract: NTPDase1 is the major enzyme regulating nucleotide metabolism at the surface of VSMCs and thus contributes to the local regulation of vascular tone by nucleotides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
82
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 48 publications
11
82
0
Order By: Relevance
“…Pharmacological [272] or pathological [119] manoeuvres that impair P2X1 receptor signalling will also blunt whole kidney autoregulation of blood flow, both in vivo and in vitro. Finally, mice with a targeted deletion of the ectonucleotidase NTPDase1 exhibit enhanced pressureinduced vasoconstriction in the mesenteric artery [183]. This probably reflects the prolonged half-life of extracellular ATP and is consistent with a key role for local nucleotide signalling in the general myogenic response.…”
Section: Myogenic Responses To Altered Perfusion Pressuresupporting
confidence: 55%
“…Pharmacological [272] or pathological [119] manoeuvres that impair P2X1 receptor signalling will also blunt whole kidney autoregulation of blood flow, both in vivo and in vitro. Finally, mice with a targeted deletion of the ectonucleotidase NTPDase1 exhibit enhanced pressureinduced vasoconstriction in the mesenteric artery [183]. This probably reflects the prolonged half-life of extracellular ATP and is consistent with a key role for local nucleotide signalling in the general myogenic response.…”
Section: Myogenic Responses To Altered Perfusion Pressuresupporting
confidence: 55%
“…It furthermore controls endothelial P2Y receptor-dependent vasorelaxation [49]. In addition, NTPDase1 is the major enzyme regulating nucleotide metabolism at the surface of vascular smooth muscle cells and thus contributes to the local regulation of vascular tone by nucleotides [49,50]. Enzymes capable of the specified catalytic reaction are highlighted with a colored background box.…”
Section: General Properties and Functional Rolementioning
confidence: 99%
“…Commercially available ligands do not discriminate well between P2Y 2 and P2Y 4 receptors, and the default position is that one or both are expressed in tissues where responses to UTP (P2Y 2/4 agonist, weak P2Y 6 agonist) are demonstrated. However, the use of P2Y 6 receptor knockouts showed that the contractile response to UTP in mouse aorta was mediated via P2Y 6 receptors and not via P2Y 2 receptors, which were shown by RT-PCR to be expressed in the smooth muscle (Bar et al, 2008;Kauffenstein et al, 2010a). Similarly, the use of knockouts and antisense oligonucleotides showed the functional expression of vasocontractile P2Y 4 and P2Y 6 but not P2Y 2 receptors in mouse mesenteric arteries and cerebral arterioles (Vial and Evans, 2002;Bar et al, 2008;Kauffenstein et al, 2010a;Brayden et al, 2013).…”
Section: Introductionmentioning
confidence: 99%